REGULATING THE FLOW OF TRANSPORT WITH ALLOWANCE FOR THE INTERVAL OF MOTION - Hul, Аndrew (Proceedings of National Aviation University (archive), 2017)
Purpose: We show that the regulation of traffic is especially important under conditions of infrastructure. The aim was to show that the objectives of traffic light regulation is to minimize and, where possible, exceptions meetings conflicting streams of vehicles. The authors show that the applied aspects of optimization of traffic lights is to eliminate mash situation and ensure the safety of all road users. Methods: The method used in the comparison is to select the best technical solution, feasibility to test mathematical tools and engineering for the practical implementation of the proposed technical solution. Results: The results of the study is repeated then that shows the organization of the preconditions for the introduction of traffic light regulation based on the calculation cycle of the traffic light object. It is proposed to cycle more than 120 seconds, as if waiting longer allowing drivers can count signal lights faulty and start moving to the blocking signal. The main tasks of traffic light regulation is to minimize and, where possible, exceptions meetings conflicting streams of vehicles and eliminate mash situation and ensure the safety of all participants. An important part of the work on the introduction of traffic light regulation is the calculation cycle of the traffic light object. For reasons of safety, cycle time of more than 120 is considered unacceptable, since the longer waiting signal allowing drivers can count faulty lights and start moving to the prohibitive signal. Discussion: In conclusion, the article revealed that the divergent forms of regulation of the intersection can also be used for general stress on public roads. The methods of testing for the road tion type.